Factors that Influence Customer Satisfaction with Kitha Sukardi Hamdani's Geprek Chicken - Tarigan, Natalia Karolina; Habiburahman, Habiburahman (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study will identify and analyze the elements that influence consumer satisfaction at Ayam Geprek Kitha Sukardi Hamdani. This study uses an unknown number of consumers of Crushed Chicken Kitha Sukardi Hamdani, so the sampling approach used is the theory of hair, and the research sample is 100 consumers. Researchers collect data from primary sources, especially questionnaire given to respondents, then tested using SPSS version 25 with multiple linear regression tests, determinants tests, partial tests, simultaneous tests. assessing research conclusion using multiple linear analysis. Based on the results of the study, it is clear that all elements, including product quality, price, location, and service quality, can affect consumer satisfaction at Ayam Geprek This is the story of Kitha Sukardi Hamdani.